Perencanaan Pembiayaan Pendidikan Untuk Peningkatan Mutu SD Negeri Dadapayam 02 - Lestari, Windah; Murniati, Ngurah Ayu Nyoman; Abdullah, Ghufron (Media Manajemen Pendidikan, 2025)
Dadapayam 02 Public Elementary School received the BOS Performance Award for two consecutive years despite its suboptimal accreditation. This was due to the school's improved performance, demonstrated by its improved educational report card scores. Based on this, a study was conducted to describe educational financing planning to improve the quality of elementary schools. This study used a qualitative approach with a case study method. Data collection was conducted through observation, interviews, and document analysis. Participants in this study were the principal, vice principal, BOS treasurer, teachers, and school committee representatives. The results showed that financing planning at Dadapayam 2 Public Elementary School had been carried out through the stages of needs analysis, priority setting, and budget preparation. However, several challenges arose, such as limited BOS funds as the primary source and the lack of active participation from external parties. Nevertheless, the school successfully prioritized improving teacher competency, followed by improving infrastructure and developing curriculum and extracurricular programs. The conclusion of this study is that structured financing planning can significantly improve the quality of education at Dadapayam 02 Public Elementary School, especially when the budget is allocated to programs that directly impact the quality of teaching and learning. Suggestions for further research are to develop a more innovative and effective funding source diversification model..